2018
DOI: 10.1186/s12870-018-1244-2
|View full text |Cite
|
Sign up to set email alerts
|

Diel pattern of circadian clock and storage protein gene expression in leaves and during seed filling in cowpea (Vigna unguiculata)

Abstract: BackgroundCowpea (Vigna unguiculata) is an important source of protein supply for animal and human nutrition. The major storage globulins VICILIN and LEGUMIN (LEG) are synthesized from several genes including LEGA, LEGB, LEGJ and CVC (CONVICILIN). The current hypothesis is that the plant circadian core clock genes are conserved in a wide array of species and that primary metabolism is to a large extent controlled by the plant circadian clock. Our aim was to investigate a possible link between gene expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…1f). Peak expression towards the end of the day was also reported for Arabidopsis 51 , soybean 16 or cowpea 17 . In our case, the expression pattern in iRNA::PhGI1 lines was similar to wildtype plants however, peak expression was advanced by three hours in all three transgenic silenced lines (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…1f). Peak expression towards the end of the day was also reported for Arabidopsis 51 , soybean 16 or cowpea 17 . In our case, the expression pattern in iRNA::PhGI1 lines was similar to wildtype plants however, peak expression was advanced by three hours in all three transgenic silenced lines (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…This pattern is similar to that observed in Arabidopsis, were under long day conditions (16:8 LD), GI mRNA peaks at ZT 10 and lowest expression www.nature.com/scientificreports www.nature.com/scientificreports/ levels occur at ZT 0 30 . Other examples of an evening phased expression pattern for GI include cowpea 17,52 and soybean 16 . In Arabidopsis, CCA1 binds to the G1 promoter and reduces its expression, which only rises towards midday, when CCA1 expression is repressed by TOC1 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It defines the timing of floral scent emission in a variety of plants including Petunia or Nicotiana attenuatta (Fenske et al , 2015; Yon et al , 2015; Terry et al , 2019). The plant circadian clock appears to have a specific transcriptional structure in different tissues such as leaves, pods, seeds, or roots (Thain et al , 2002; James et al , 2008; Bordage et al , 2016; Weiss et al , 2018). As the transcriptional structure of the clock in petal is currently unknown, we used Petunia hybrida to perform a detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…upregulated in drought-tolerant cultivars from different crops under water deficit conditions (Sato and Yokoya, 2008;Temel et al, 2017). For comparison, VuEF1-α and VuPp2A genes were selected as reference genes due to their stability under drought stress conditions (Da Silva et al, 2015;Weiss et al, 2018). Gene expression analysis by qPCR revealed that both DG genes were mostly expressed at 25% and 0% of FC treatments (Fig.…”
Section: Could Gene-expression Profiling Be Used To Screen Cowpea Dromentioning
confidence: 99%